BLACK BOX TESTING WITH THE EQUIVALENCE PARTITIONING AND CAUSE EFFECT GRAPH METHOD IN ARCHIVE INFORMATION SYSTEM - Ismiati, Suci; Aditiawan, Firza Prima; Nurlaili, Afina Lina (Informatika, Universitas Jenderal Soedirman, 2024)
The Wijaya Putra University Archives Information System is a website-based information system used by Wijaya Putra University teaching staff as a digital archive storage medium. Several users mentioned that there were errors in the system, such as login problems, data access problems, and no file delivery notifications, so testing was needed to find functional errors in the system so that repairs could be made. Testing was carried out using the Black Box method with Equivalence Partitioning and Cause Effect Graph techniques. The use of Equivalence Partitioning is used to divide data input into each form, and each form input will be tested and grouped based on its function, whether it is appropriate or not appropriate. Meanwhile, the Cause Effect Graph is used to find out whether the test results obtained from the Equivalence Partitioning process are in accordance with the relationship between cause (input) and effect (output) expected in the system. Based on the research conducted, the final results show that out of a total of 58 test cases, there were 50 appropriate test cases and 8 inappropriate test cases, resulting in an effectiveness value of 87.67%. With this value, the Wijaya Putra University Archives Information System is running according to its function, but still needs to be repaired and further developed for functions that still have errors.